Effect of Replacing Sorghum Stubble with Tillandsia recurvata (L.) on Liveweight Change, Blood Metabolites, and Hematic Biometry of Goats - Héctor G. Gámez-Vázquez (Biology, 2022)
Tillandsia recurvata is an epiphyte that grows on the canopy of many trees in tropical and subtropical areas of America. The objective of this study was to evaluate the effect of partial or complete substitution of sorghum stubble with T. recurvata on liveweight change, metabolic profile, and complete blood count of goats fed increasing levels (0, 30, and 60%, dry matter basis) of T. recurvata. Thirty non-pregnant three-year-old, non-lactating, healthy mixed-breed goats, ten animals per treatment (T0, T30, and T60), were adapted to diets and facilities for 14 days (d-14). Blood samples were collected at d-15, 28, and 56. At the last phase of the trial (from days 67 on), control goats tended to gain more (p = 0.09) weight than their counterparts consuming T. recurvata. Plasma protein, glucose, triglycerides, calcium, and phosphorus concentrations did not differ among dietary treatments (p > 0.05). Dietary treatment influenced red blood cells (higher for T60; p < 0.01), white blood cells (higher for T30; p < 0.05), mean corpuscular volume (higher for T0; p < 0.001), and mean corpuscular hemoglobin concentration (higher for T0; p < 0.01), although not the rest of the blood variables (p > 0.05). The hematocrit percentage tended to be higher (p = 0.06) in T30 than T0 and T60. It was concluded that replacing sorghum stubble with T. recurvata did not modify the metabolic status and maintained live weight of goats. Nevertheless, the use of T. recurvata as feed for goats would improve the nutrition of these animals in the dry season compared to the current diet obtained from an arid rangeland, reducing production costs, and would alleviate the damage caused by this aggressive epiphyte to host trees.